Is a Compromise Between the Minority and the Majority Possible? - Birgiel, Paulius (Lietuvos istorijos studijos, 2023)
Rec.: Kari Alenius, Saulius Kaubrys, Balancing Between National Unity and Multiculturism: National Minorities in Lithuania and Finland 1918–1939, Paderborn: Brill Schoning, 2022.
Keywords: -